A Computerized Family Planning Counseling Aid: A Pilot Study Evaluation of Smart Choices. Issue 1 (21st February 2017) - Koo, Helen P.; Wilson, Ellen K.; Minnis, Alexandra M.
Abstract: CONTEXT: Resource constraints may make it challenging for family planning clinics to provide comprehensive contraceptive counseling; technological tools that help providers follow recommended practices without straining resources merit evaluation. METHODS: A pilot study using a two‐group, posttest‐only experimental design evaluated Smart Choices, a computer‐based tool designed to help providers offer more patient‐centered counseling and enable patients to participate proactively in the counseling session. In two North Carolina family planning clinics, 214 women received usual counseling in March–May 2013, and 126 women used Smart Choices in May–July 2013. Exit interviews provided data for the evaluation. Multivariate Poisson and multinomial logistic regression analyses were performed to examine group differences in counseling outcomes. RESULTS: Three of 12 hypotheses tested were supported: Compared with controls, women in the intervention group knew more contraceptive methods (adjusted mean, 11.1 vs. 10.7); discussed more topics related to sexual health during counseling (1.2 vs. 0.9 among those reporting any discussion); and rated counseling as more patient‐centered, an indication of how well they felt providers understood their family planning circumstances and ideas (3.9 vs. 3.7 on a scale of 1–4). Contrary to another hypothesis, controls were more likely than women in the intervention group to choose IUDs and implants. CONCLUSIONS: Computerized counseling aids like Smart Choices are in an early stage of development. Future research is warranted to develop tools that lead to more productive and individualized clinic visits and, ultimately, to more effective contraceptive use and reduced levels of unintended pregnancy.